Analisis pendapatan usaha gula aren di Desa Cawang Lama Kabupaten Rejang Lebong - Febri Nur Pramudya; Putri Milanda Bainamus; Adnan (Fakultas Pertanian Universitas Majalengka, 2023)
The aim of this research was to analyze palm sugar business income in Cawang Lama Vilage, Rejang Lebong Regency. The location was chosen purposively because this area is a large producer of palm sugar and runs its business sustainably. This research method was obtained from quantitative data and questionnaires from research respondents. This research was carried out purposively in Cawang Lama Village. The things analyzed in this research are income and efficiency values. The results of the analysis showed that the income obtained was IDR1,093,383.-. This is influenced by the amount of revenue and production costs incurred each month. This income is relatively small but helps the family's economy, because palm sugar in this area is mostly produced only as a side job. Due to limited raw materials and the area of ​​oil palm plantations owned. On average, they work as coffee farmers and rice farmers as their main job. The palm sugar business in one of the largest palm sugar producing villages in Selupu Rejang District has an efficiency value of 1.56, which means the business is feasible to run. It can be concluded that the palm sugar business in Cawang Lama Village, Rejang Lebong Regency has good business feasibility, and every unit of costs incurred in this business can be returned 1.56 times.